KEANEKARAGAMAN JAMUR PADA KETINGGIAN TEMPAT YANG BERBEDA DI KAWASAN HUTAN LINDUNG DI DESA BELANGIAN KECAMATAN ARANIO KABUPATEN BANJAR - Dina Naemah; Susilawati Susilawati (Universitas Lambung Mangkurat, 2011)
Fungi is one of the non-timber forest which grows naturally and can be partially cultivated. Fungi that grow in nature widely known by the people who live in and around the forest. Fungi are known in everyday life, although not as good as any other plants. That's because fungi grow only at certain times, on certain conditions that support, and long life are limited. Fungi are the object of this study are fungi that have fruiting bodies and can be seen by naked eye at the time of the study in the observation plots. The research was carried out on a protected forest in Belangian Village of Aranio District, Banjar Regency. Object is observed from this study is a fungus that grows and lives inside the quadrats were both contained in the forest floor as well as those found on tree trunks. The method used in this study using a single plot. Fungus that is in the quadrats were divided into 3 divisio the Basidiomycota, Ascomycota and Myxomycota, fungi that were encountered are from divisio Basidiomycota. Mushrooms are found consisting of 10 orders of Russulales, Agaricales, Polyporales, Poriales, Hymenochaetales, Cantharellales, Boletales, Auriculariales, Pezizales and Protosteliales with 21 families consisting of Stereaceae, Marasmiaceae, Crepidotaceae, Clitocybecae, Lycoperdaceae, Mycenaceae, Hygrophoraceae, Hapalopilaceae, Ganodermataceae , Fomitopsidaceae, Polyporaceae, Microporellaceae, Albatrellaceae, Poriceae, Hymenochaetaceae, Hydnaceae, Cantharellaceae, Coniophoraceae, Auriculariaceae, Sarcoscyphaceae, Ceratomyxaceae. Species found at an altitude of 200 m above sea level amounted to 37 species, at an altitude of 300 m above sea level and at an altitude of 2 types of 400 m asl 2 types, so that the whole of fungus that is found totaled 41 species in all three heights.